The relationship between exposure to Soul City Educational Programme and knowledge and practices of South African women aged 16-65 years on cancer of the cervix - Moremi, Lemphi Mayoyo (My University, 2010)
Background: Soul City Institute for Health and Development Communication (SC IHDC), a Non Governmental Organisation (NGO) set up to promote health through media tackled cervical cancer in 2006. The Soul City cervical cancer educational programme was developed and broadcasted on South African Broadcasting Cooperation (SABC1) television and radio stations across the country. This paper assesses the relationship between exposure to educational programme and knowledge and practise of South African women on cervical cancer. Objective: To investigate if there is an association between exposure to Soul City educational programme on cervical cancer and knowledge and practice of South African women in relation to cervical cancer. Methods: An analytical cross sectional study design was employed. Secondary data from a Soul City study was used and all South African women aged 16 – 65 years who enrolled into the 2006 leg of the study were included. The data was analysed using Stata 9 utilising logistic regression models. Results: There were 1013 women aged between 16 and 65 years in this study and the average age was 35 years. Most women lived in metropolitan areas (53%), were employed (41%), had secondary education (74%) and had knowledge about cervical cancer and Pap smear (>50%). Lack of knowledge about cervical cancer and Pap smear was observed amongst rural residents (>60%), illiterate women (>54%), and Black South African women (>54%). Generally, participation in cervical screening was low among these women. The iv majority of women had never been screened for cervical cancer in the past (49%) as well as in the previous 12 months (79%). However, a higher proportion of women aged 30 years and above had been for cervical screening test in the past (59%). Although many women aged 30 years and above had been screened sometime in the past, more than three quarters of them were not screened in the last 12 months. Low uptake of Pap smear in 2006 was observed amongst rural residents (6%), older women (9%), illiterate (4%), Coloured (20%) and Black (20%) South African women. Overall knowledge about cervical cancer and Pap smear was associated with exposure to Soul City educational programme on cervical cancer through different media more especially television. Women who watched Soul City on television were more likely to have knowledge about cervical cancer (OR = 1.97, and 95% CI = (1.12; 3.47)) and Pap smear (OR = 2.08, and 95% CI = (1.24; 3.47)) than those who did not watch the programme. Participation of women aged 30 years and above in cervical cancer screening in 2006 was not associated with exposure to the Soul City educational programme. Conclusion: The study findings suggest that Soul City educational programme is associated with knowledge about cervical cancer and Pap smear. There was no evidence that exposure to Soul City educational programme was associated with participation in cervical cancer screening in 2006.
MSc(Med), Epidemiology and Biostatistics, Faculty of Health Sciences, 2009
Keywords: cervical cancer; South African women